Synthesis of porous polymer/tissue paper hybrid membranes for switchable oil/water separation - Cong-Xiao Cao (Nature Portfolio, 2017)
Abstract The unusually broad physical and chemical property window of ionic liquids allows for a wide range of applications, which gives rise to the recent spring-up of ionic liquid-based functional materials. Via solvothermal copolymerization of a monomeric ionic liquid and divinylbenzene in the presence of a tissue paper in autoclave, we fabricated a flexible porous polymer/paper hybrid membrane. The surface areas of the hybrid membranes depend on the weight fraction of the copolymer impregnated inside the tissue paper. The as-prepared hybrid membrane shows controlled surface wettability in terms of ethanol wetting and ethanol removal by harsh drying condition. This unique property provides the hybrid membrane with switchable oil/water separation function, thus of practical values for real life application.